Carrying a secret in my heart-- : children of the victims of the reprisals after the Hungarian Revolution in 1956 : an oral history - Kőrösi, Zsuzsanna (Central European University Press, 2003)
For a decade now, the authors have been conducting interviews for Hungary's Oral History Archives, with the children of those Hungarians - national heroes, as they are generally seen today - who were imprisoned for their involvement in the 1956 revolution. The vast body of material that has been collected, and is now at the disposal of sociologists, psychologists and others in the academic community, forms the basis of this volume. This is a documentation of memories of the revolt and, more particularly, its aftermath. The virtually spontaneous ten-day uprising exerted a lasting effect on the fates of the families of the more than 20,000 who were imprisoned and 229 executed by the regime in the harsh reprisals that followed the crushing of the revolution (the last of them as late as the early 1960s), with active police surveillance extended to tens of thousands more. This intimidation, and the attendant social and economic devastation that it wrought, bore especially hard on the psyches, upbringing and education, and hence the subsequent opportunities and life courses of the children who grew up within those families. The material is grouped by theme: e.g. the effects on communication within families, changes in social status, how relatives and friends reacted, and what sorts of problems these children encountered in pursuing their studies, in trying to assimilate into society as adults, and in relating to those fathers who did return. In an appendix, the editors present detailed biographies of the people most directly affected, offering an unparalleled glimpse into the fates of those they interviewed. The documentation includes letters that the children wrote to their imprisoned fathers.